Muscle in vein conduits: our experience - Minini, Andrea; Megaro, Almerico (Acta Biomedica Atenei Parmensis, 2021)
Muscle in vein (MIV ) conduits have gradually been employed in the last 20 years as a valuable technique in bridging peripheral nerve gaps after nerve lesions who cannot undergo a direct tension-free coaptation. The advantages of this procedure comparing to the actual benchmark (autograft) is the sparing of the donor site, and the huge availability of both components (i.e. muscle and veins). Here we present a case serie of four MIV performed at our hospital from 2018 to 2019. The results we obtained in our experi-ence confirmed its effectiveness both in nerve regeneration (as sensibility recovery) and in neuropathic pain eradication. Our positive outcomes encourage its use in selected cases of residual nerve gaps up to 30 mm